2022
DOI: 10.4103/jigims.jigims_33_22
|View full text |Cite
|
Sign up to set email alerts
|

Patient Safety vis-à-vis Safe Surgery

Abstract: Today, patient harm due to unsafe care is a large and growing global public health challenge and is one of the leading causes of death and disability worldwide. Most of this patient harm is avoidable. As countries strive to achieve universal health coverage and the Sustainable Development Goals, the beneficial effects of improved access to health services can be undermined by unsafe care. The benefits of having a strategic and coordinated approach to patient safety, addressing the common causes of harm, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Previous studies showed that transformational leadership has a significant impact on patient safety culture and the perceived level of patient safety. 37 , 54 , 55 Moreover, many studies declared that patient safety culture has a positive impact on patient safety perceptions and outcomes. 8 , 11 , 56 The current study revealed that transformational leadership and patient safety culture has also significant association with nurses’ practices related to patient safety.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that transformational leadership has a significant impact on patient safety culture and the perceived level of patient safety. 37 , 54 , 55 Moreover, many studies declared that patient safety culture has a positive impact on patient safety perceptions and outcomes. 8 , 11 , 56 The current study revealed that transformational leadership and patient safety culture has also significant association with nurses’ practices related to patient safety.…”
Section: Discussionmentioning
confidence: 99%